EMOTIONAL BOUNDARIES IN SLAVERY EXPERIENCED BY THE MAIN CHARACTER IN THE NOVEL "THE WATER DANCER" BY TA-NEHISI COATES - Dahlan, Dahlan; Annisa, Nurifka (Journal of Islamic Culture and Literature (JICeL), 2025)
This study explores the psychological dimensions of emotional boundaries depicted in Ta-Nehisi Coates’ novel The Water Dancer, focusing on the experiences of enslaved individuals. Using qualitative analysis, the research delves into the emotional landscapes of the characters, particularly Hiram Walker, to understand how they navigate trauma, identity, and resilience. Drawing on Freud’s psychoanalytic theory, the analysis highlights the dual role of emotional repression as a survival mechanism and the potential long-term psychological impacts it may entail. The findings reveal the profound psychological complexities faced by Hiram Walker and other enslaved individuals, emphasizing the significance of emotional boundaries as coping mechanisms in dealing with trauma, fear, and oppression. At the same time, the analysis uncovers the conflict between the desire for emotional connection and the need for self-protection.This research aims to provide valuable insights into the psychological impact of slavery, encompassing aspects of trauma, resilience, and identity formation. Keywords: Emotional Boundaries, Psychological impact, identity.